Customer loyalty as the key driver of business performance: evidence from digital marketing, service quality, and pricing strategy in online gaming services - Genta Aditya; Suhardi Suhardi; Mat Amin (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of digital marketing strategies, service quality, and pricing strategies on business performance with customer loyalty as a mediating variable in online gaming services. The approach used was quantitative with an explanatory research design, with data collected through purposive sampling from users of Mobile Legends boosting services. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results showed that digital marketing strategies, service quality, and pricing strategies significantly influenced customer loyalty, with pricing strategy being the most dominant factor. Customer loyalty was proven to have a significant effect on business performance. However, digital marketing only had a weak direct effect, and service quality did not significantly influence business performance. Furthermore, customer loyalty was able to mediate the influence of digital marketing and pricing strategies on business performance, but not on service quality. These findings confirm that in a competitive digital environment, business performance is more determined by customer loyalty and perceived value than service quality alone.